The black box of schooling. A cultural history of the classroom - Sambola Alcobé, Rosa (Historia y Memoria de la Educación, 2016)
Review of the book: Sjaak Braster, Ian Grosvenor y María del Mar del Pozo (eds.) The black box of schooling. A cultural history of the classroom. Bruselas: P.I.E - Peter Lang, 2011, 330 páginas. ISBN: 978-90-5201-760-0.